Ripe for a Big Bang? Assessing the Political Feasibility of Legislative Reforms in the Philippines’ Local Government Code - Matsuda, Yasuhiko (2012)
In the Philippines' highly decentralized political system, smooth functioning of inter-governmental relations is key to effective service delivery and good governance overall. Although considered a milestone, the 1991 Local Government Code, the Philippines' basic legislation governing inter-governmental relations, contains provisions that thwart vertical and horizontal resource equalization among local government units, and contributes to mismatch between expenditure assignments and the fiscal capacities of the local government units. Numerous technical reports have called for adjustments to the existing revenue and expenditure assignments, yet no tangible progress has been made. This paper assesses the prospects of legislative reforms on the revenue side of the decentralization framework. Using a variety of approaches ranging from a historical analysis to institutional analysis of the legislative dynamics in the Philippine congress, it assesses the prospects of a major overhaul of the Local Government Code and concludes that a significant reform is highly unlikely under the conditions prevailing in the late 2010s. By implication, any effort to improve the Philippines' inter-governmental framework will have to settle for sub-optimal incremental measures within the inefficient revenue assignment arrangement.